Question: Prove that: \dfrac{cos2A}{1+ sin2A} = \dfrac{1- tanA}{1+ tanA}

Solution:

Taking LHS,

= \dfrac{cos2A}{1+ sin2A}

Expanding cos2A and sin2A and identity of 1

= \dfrac{cos^2A - sin^2A}{sin^2A + cos^2A + sin2A}

Performing simple mathematical operations

= \dfrac{(cosA + sinA)(cosA - sinA)}{(cosA + sinA)^2}

= \dfrac{cosA - sinA}{cosA + sinA}

Dividing each term by cosA

= \dfrac{\frac{cosA}{cosA} - \frac{sinA}{cosA} }{\frac{cosA}{cosA} + \frac{sinA}{cosA}}

We know, [\frac{sinA}{cosA} = tanA]

= \dfrac{1 - tanA}{1 + tanA}

= RHS

#proved